The Careers and Professional Well-Being of Women Oncologists During the COVID-19 Pandemic: Responding for Tomorrow - Shivani Majmudar; Stephanie L Graff; Marah Kays; Beatriz X Braz; Laurie Matt-Amaral; Merry J Markham; Ishwaria M Subbiah; Emily Bergsland; Shikha Jain (JMIR Publications, 2023)
The COVID-19 pandemic exacerbated gender inequity in medicine, with women physicians reporting greater household responsibilities than their men counterparts and steeper barriers to career advancement. The pandemic highlighted the systemic assumptions and challenges faced by women physicians, which we anticipate is also true in our field of oncology. Prior literature suggests that women physicians were tasked with increased personal and professional responsibilities without compensation for their additional work, as well as derailments in career progression and significant burnout. Our aims are to highlight areas of opportunity to optimize the workplace experience of the oncology workforce and to invest in the professional well-being and sustainability of women oncologists as a step toward global workplace equity and future pandemic preparedness.